Development And Evaluation Of Topical Ethosomal Formulation Composed Of Orthosiphon Stamineus Extract For Melanoma - Vishkaei, Mansoureh Nazari (2019)
Melanoma is one of the most aggressive types of skin cancer with high rate of fatality if left untreated. Herbal-based compounds can be useful as alternative in cancer therapy such as melanoma due to their high anti-oxidant and anti-inflammatory properties. These characteristic features can halt angiogenesis, a process of new blood vessels formation which is crucial for tumor growth and metastasis. However, poor bioavailability due to the high polarity of the phythochemicals limits their effectiveness. Orthosiphon stamineus (O.S) is a popular medicinal herb found in South East Asia and a unique solvent extract of this herb has been shown to have antiangiogenic activity. In this study, the extract of O.S standardized to 6% rosmarinic acid was formulated into a liposomal type of formulation known as ethosome. Both the extract and the formulation were evaluated for their effectiveness towards melanoma in vitro and in vivo and pharmacokinetics, toxicology and physico-chemical properties were evaluated.